2016
DOI: 10.1097/01.jaa.0000484311.96684.0c
|View full text |Cite
|
Sign up to set email alerts
|

PA and NP productivity in the Veterans Health Administration

Abstract: This study assessed the 2014 clinical productivity of 5,959 physician assistants (PAs) and nurse practitioners (NPs) in the US Department of Veterans Affairs' Veterans Health Administration (VHA). Total work relative value units divided by the direct clinical full-time equivalent measured annual productivity, and correlated factors were examined using weighted analysis of variance. PAs and NPs in adult primary care roles were more productive than those in other specialties. Both providers were more productive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…Other than some minimal regional associations, state-level factors were not associated with PCP provider type. Our finding that the type of PCP assigned to a patient was not affected by state SOP is consistent with recent findings that SOP regulations were not associated with productivity in the VHA 58 or with practice patterns and care quality in Community Health Centers. 59 …”
Section: Discussionsupporting
confidence: 92%
“…Other than some minimal regional associations, state-level factors were not associated with PCP provider type. Our finding that the type of PCP assigned to a patient was not affected by state SOP is consistent with recent findings that SOP regulations were not associated with productivity in the VHA 58 or with practice patterns and care quality in Community Health Centers. 59 …”
Section: Discussionsupporting
confidence: 92%
“…What PAs and NPs do, how well they do it, and what impact this has on patient-centered results are a needed piece of health service research [11, 19, 20, 24, 31]. One finding in this study revealed that a great number of tasks performed by a PA and NP in Dutch hospitals were not visible to administrators due to lack of documentation or registration.…”
Section: Discussionmentioning
confidence: 94%
“…Studies also show that there is wide variation across different types of organizations in their productivity (Xue & Tuttle, 2017), CHCs in particular (Park et al, 2020). Others include primary and specialty care at the Veteran Health Administration (Moran et al, 2016) and oncology settings (Moote et al, 2012). The purpose of this study is to explore why this variation occurs in the context of CHCs.…”
Section: Introductionmentioning
confidence: 99%
“…This average, however, may be obscuring the potential to enhance NP’s and PA’s productivity by modifying policies and practices, be they at the federal, state, or organizational levels. Moran et al (2016) examined factors influencing NP and PA productivity in the context of primary and specialty care at the Veterans Health Administration (VHA), where the use of both professions has also grown dramatically. While their approach differed from ours (they measured productivity using RVUs and at the individual level), they found that practice settings were key explanatory factors associated with productivity.…”
Section: Introductionmentioning
confidence: 99%